Comparison of Knowledge and Traditional Medicine Use Patterns Among Health and Non-Health Students in Medan City - Wahyudi Wahyudi; Iqbal Fathur Rifqy; Zahra Kayla Mazril; Nabila Fatila (PROMOTOR, 2024)
Traditional medicine is an ingredient or concoction made from elements in the form of plants, animals, minerals, extract preparations (galenic), or a mixture of these ingredients, which has been used for treatment for generations. This research aims to describe the knowledge and patterns of use of traditional medicine among health and non-health students. This research is descriptive quantitative research using survey methods. Data was collected using a questionnaire via Google form, which was then analyzed to describe the research results. The research results showed that 43.86% of health students understood and comprehended traditional medicine knowledge, while 24.5% of non-health students had low knowledge of traditional medicine. The pattern of traditional medicine use by health students is 76.87% lower than that of non-health students, who use traditional medicine patterns as much as 80.96%. The conclusion of this research is that the level of knowledge regarding traditional medicine is better in health students at around 43.86% compared to non-health students, and the pattern of effort to use traditional medicine is more significant in non-health students at 80.96% than in health students.